Konwencjonalne i emocjonalne w poezji Małgorzaty Hillar - Przymuszała, Beata (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
Text, showing the most important ways in the 20th century to think about poetry, refers to modernist epiphany (Ryszard Nycz). On the example of Małgorzata Hillar’s poetry, the author shows the inadequacy of this concept. It focused on the linguistic aspect of transmitting emotions, bypassing their bodily sensations. The recent studies on the relationship between emotions and language also allow to present a relationship with language and poetry. Recent studies on the relationship between emotions and language also allow us to otherwise present the relationship between language and poetry.